Neuropathological and cerebrospinal fluid correlates of choroid plexus inflammation in progressive multiple sclerosis - Magliozzi, R.; Hametner, S.; Mastantuono, M.; Mensi, A.; Karimian, M.; Griffiths, L.; Watkins, L. M.; Poli, A.; Berti, G. M.; Barusolo, E.; Bellini, B.; Rossi, S.; et al. (Brain pathology (Zurich, Switzerland), 2025)
Among the intrathecal inflammatory niches where compartmentalized inflammation persists and plays a pivotal role in progressive multiple sclerosis (MS), choroid plexus (CP) has recently received renewed attention. To better characterize the neuropathological/molecular correlates of CP in progressive MS and its potential link with other brain inflammatory compartments, such as perivascular spaces and leptomeninges, the levels, composition and phenotype of CP immune infiltration in lateral ventricles of the hippocampus were examined in 40 post‐mortem pathologically confirmed MS and 10 healthy donors, using immunochemistry/immunofluorescence and in‐situ sequencing. Significant inflammation was detected in the CP of 21 out of the 40 MS cases (52%). The degree of CP inflammation was found correlated with: number of CP macrophages (R: 0.878, p = 1.012 x 10‐13) and high frequency of innate immune cells expressing the markers MHC‐class II, CD163, CD209, CD11c, TREM2 and TSPO; perivascular inflammation (R: 0.509, p = 7.921 x 10‐4), and less with meningeal inflammation (R: 0.365, p = 0.021); number of active lesions (R: 0.51, p: 3.524 x 10‐5). However, it did not significantly correlate with any clinical/demographic characteristics of the examined population. In‐situ sequencing analysis of gene expression in the CP of 3 representative MS cases and 3 controls revealed regulation of inflammatory pathways mainly related to ‘type 2 immune response’, ‘defense to infections’, ‘antigen processing/presentation’. Analysis of 78 inflammatory molecules in paired post‐mortem CSF, the levels of fibrinogen (R: 0.640, p = 8.752 x 10‐6), PDGF‐bb (R: 0.470, p = 0.002), CXCL13 (R: 0.428, p = 0.006) and IL15 (R: 0.327, p = 0.040) were correlated with extent of CP inflammation. Elevated fibrinogen and complement deposition were found in CP and in underlying subependymal periventricular areas, according to “surface‐in” gradient associated with concomitant prominent microglia activation. CP inflammation, predominantly characterized by innate immunity, represents another key determinant of intrathecal, compartmentalised inflammation persisting in progressive MS, which may be possibly activated by fibrinogen and influence periventricular pathology, even without substantial association with clinical features. Graphical representation of the widespread white matter (blue color mask) and grey matter (cortical and deep grey matter; red color mask) demyelination in MS cases characterized by substantial inflammation of the CP (A). The presence of lesions was mainly associated with periventricular white matter and hippocampus areas (A). Spearman correlation analysis (B) between CP inflammation and the other quantified neuropathological parameters shows significant positive correlation (darker red) between degree of CP inflammation and degree of perivascular inflammation (R: 0.509, p: 7.921 × 10−4), with meningeal inflammation (R: 0.365, p: 0.021) and with the number of active lesions (R: 0.51, p: 3.524 × 10−5) identified in the surrounding periventricular areas (B). Extensive subependymal active demyelination (C) with intense microglia activation, characterized by expression of MHC‐class II, TMEM119, CD163, and iNOs (D–H) were detected in the hippocampus. Spearman correlation analysis between degree of CP inflammation and clinical features of the examined MS cases did not reveal any significant correlation (I). Survival analysis that compared the populations with (red line) and without (blue line) CP inflammation, with respect to the age at death did not found significantly difference (p: 0.391), even if a higher percentage of subjects without CP inflammation were characterized by later age at death (J). Scale bars: 500 μm (C), 200 μm (D),100 μm (E–I).